MoS2-based ferroelectric field-effect transistor with atomic layer deposited Hf0.5Zr0.5O2 films toward memory applications - Ming-Yang Cha; Hao Liu; Tian-Yu Wang; Lin Chen; Hao Zhu; Li Ji; Qing-Qing Sun; David Wei Zhang (AIP Advances, 2020)
Recently, hafnium oxide (HfO2)-based ferroelectric materials have achieved phenomenal success in next-generation nonvolatile memory applications. In this study, we fabricated Hf0.5Zr0.5O2 (HZO) ferroelectric capacitors and back-gate field-effect transistors (FETs) with few-layered molybdenum disulfide (MoS2) nanosheets as the channel and a ferroelectric Hf0.5Zr0.5O2 film as the gate dielectric. Good dielectric and ferroelectric properties have been observed from the HZO film fabricated with atomic layer deposition-based techniques. The MoS2–HZO ferroelectric FETs (FeFETs) have exhibited excellent performance including ferroelectric polarization switching with a high on/off ratio and negligible degradation in endurance and retention properties. Our results shown here suggest that MoS2–HZO FeFETs can be a promising alternative for next-generation nonvolatile memories.